Non-Monotonicity of Branching Rules with Respect to Linear Relaxations - Shah, Prachi; Dey, Santanu S.; Molinaro, Marco (INFORMS Journal on Computing, 2025)
Modern mixed-integer programming solvers use the branch-and-cut framework, where cutting planes are added to improve the tightness of the linear programming (LP) relaxation, with the expectation that the tighter formulation would produce smaller branch-and-bound trees. In this work, we consider the question of whether adding cuts will always lead to smaller trees for a given fixed branching rule. We formally call such a property of a branching rule monotonicity. We prove that any branching rule which exclusively branches on fractional variables in the LP solution is nonmonotonic. Moreover, we present a family of instances where adding a single cut leads to an exponential increase in the size of full strong branching trees, despite improving the LP bound. Finally, we empirically attempt to estimate the prevalence of nonmonotonicity in practice while using full strong branching. We consider randomly generated multidimensional knapsacks tightened by cover cuts as well as instances from the MIPLIB 2017 benchmark set for the computational experiments. Our main insight from these experiments is that if the gap closed by cuts is small, change in tree size is difficult to predict, and often increases, possibly due to inherent nonmonotonicity. However, when a sufficiently large gap is closed, a significant decrease in tree size may be expected. History: Accepted by Alice E. Smith, Andrea Lodi / Design & Analysis of Algorithms–Discrete. Funding: This work was supported by Air Force Office of Scientific Research [Grant F9550-22-1-0052]. Supplemental Material: The software that supports the findings of this study is available within the paper and its Supplemental Information ( https://pubsonline.informs.org/doi/suppl/10.1287/ijoc.2024.0709 ) as well as from the IJOC GitHub software repository ( https://github.com/INFORMSJoC/2024.0709 ). The complete IJOC Software and Data Repository is available at https://informsjoc.github.io/ .